Przedsiębiorczość a bezpieczeństwo ruchu drogowego - Zbigniew Ożdżyński (Przedsiębiorczość - Edukacja, 2007)
The article presents examples of activities and enterprising attitudes researched by the author in the field of the enterprise in the improvement of the road safety.  There are also presented the examples of enterprising activities of many institutions interested in this matter - from government-institutions, including the Department of the National Education, the Department of Transport and Building, the National Council of Traffic Safety, provincial Centres of Road Traffic, the Police and schools, to the over government institutions like European Parliament and Council and private driving schools.  The author presents the system of education about traffic safety - puts emphasis on activities of the driving schools - as an example of enterprising activities. The article gives examples of protecting pedestrians in road accidents. The article compares also the chosen indicators concerning traffic accidents in Poland and in chosen countries of the European Union in years 2000-2004.